Tinjauan Sosiologistentang Partisipasi Masyarakat Kampung Naga Kabupaten Tasikmalaya dalam Kegiatan Penimbangan Balita di Posyandu - Heri Djamiatul Maulana, Sumarni DW, Supriyati (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Community Participation in weighing children under five years old in Posyandu is important to be examined as it has an important impact toward disease prevention and promotion as well as in improvement of human resource quality and decreasing infant and maternal death through community's nutrition status improvement. Previous study showed that out of 39 children under five years old who were rarely come to Posyandu, there were 13 children who were malnourished and 1 person who had poor nutrition.Objective: This research was aimed to investigate and describe community's participation of Kampung Naga in weighing children under five years old in Posyandu from sociological perspective.Methods: This research was using qualitative design. Data was collected with focus group discussion, interview, and observation. Interview was done toward mothers of the children, kuncen, punduh, tukang jampe, head of community, village's officers, cadre, midwife and head of Primary Health Care Center. Data validity was implemented with source and method triangulation, and reliability was done with data auditing. Data analysis was carried out using content analysis.Results:The result of this research showed that community's participation of Kampung Naga in weighing of children under five years old was influenced by internal and external factors.The internal factors consist of community's value and believe, social interaction and stratification. On the other hand, the external factors of community's participation were cadre's perception, posyandu process, and social support.Conclusion: Kampung Naga Community's participation in weighing of children under five years old had strong relationship with their norms, custom, value, believe and their culture. Keywords: participation, weighing of children under five years old, Kampung Naga, sociological perspective